2019
DOI: 10.3390/nu11061292
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Atherosclerosis and Plasma Antioxidant Micronutrients or Red Blood Cell Polyunsaturated Fatty Acids in People Living with HIV

Abstract: Background: People living with human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) (PLWH) are at an increased risk of cardiovascular disease. Diet-related factors may contribute. The aim of this pilot study was to determine, in PLWH, the relationship between atherosclerosis assessed by carotid intima-media thickness (CIMT) and (A) plasma antioxidant micronutrients and oxidative stress or (B) red blood cell polyunsaturated fatty acids (RBC PUFA), particularly long chain ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Moreover, HIV seems to directly affect the antioxidant defense system [142], and HIV-related oxidative stress is a concurrent cause of HIV-associated malignancies, metabolic disorders, and premature aging [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161]. Since HIV patients have reduced levels of ASC and other micronutrients than healthy subjects , it has been suggested that ASC supplementation could help to reduce oxidative stress and slow down chronic inflammation in HIV-positive individuals [163]. However, high-dose ASC is capable of inducing some hepatic cytochromes, such as CYP3A, which can interact with antiretroviral drugs [141,164].…”
Section: Role Of Asc In the Management Of Infectious Diseasesmentioning
confidence: 99%
“…Moreover, HIV seems to directly affect the antioxidant defense system [142], and HIV-related oxidative stress is a concurrent cause of HIV-associated malignancies, metabolic disorders, and premature aging [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161]. Since HIV patients have reduced levels of ASC and other micronutrients than healthy subjects , it has been suggested that ASC supplementation could help to reduce oxidative stress and slow down chronic inflammation in HIV-positive individuals [163]. However, high-dose ASC is capable of inducing some hepatic cytochromes, such as CYP3A, which can interact with antiretroviral drugs [141,164].…”
Section: Role Of Asc In the Management Of Infectious Diseasesmentioning
confidence: 99%
“…Fourteen studies were conducted from Europe, 20,2226,30,31,34,35,39,41–43 followed by America (4 studies), 10,27,28,38 Asia (4 studies), 11,21,29,32 and Africa (4 studies). 33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th. 20,29,33,39…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of AS is not fully known, and atherogenesis involves a variety of risk factors including hyperlipidemia, hypertension, diabetes, smoking, and drinking [2]. Previous studies have reported that inflammatory response and the disorder of lipid metabolism are closely related to atherosclerosis [3], while poor dietary choices such as Western diet can also contribute to an increased risk of CVD, specifically AS [4]. Currently, treatment options for AS can be divided into interventional and noninterventional methods [5].…”
Section: Introductionmentioning
confidence: 99%